1996
DOI: 10.1111/1523-1747.ep12344976
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Expression of a Retrovirus-Transduced Gene in Human Keratinocytes

Abstract: Retroviral-mediated transfer of new genetic information into keratinocytes is a key step in epidermal gene therapy. An obstacle to the use of retroviruses for gene therapy is that although high levels of expression of the transduced gene can be maintained in tissue culture, expression is often lost when the cells are transplanted to an animal host. To examine some of the factors involved in this instability of expression, we transduced keratinocytes with a retrovirus encoding the gene for human factor IX and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
1
1

Year Published

1998
1998
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 20 publications
3
49
1
1
Order By: Relevance
“…Thus, the stable transduction of keratinocyte stem cells is essential to achieve long-term gene expression in the skin. 19,20 Until now, retroviral vectors were used in skin gene therapy. They appear to transduce up to 100% of keratinocytes in vitro, including keratinocyte stem cells.…”
mentioning
confidence: 99%
“…Thus, the stable transduction of keratinocyte stem cells is essential to achieve long-term gene expression in the skin. 19,20 Until now, retroviral vectors were used in skin gene therapy. They appear to transduce up to 100% of keratinocytes in vitro, including keratinocyte stem cells.…”
mentioning
confidence: 99%
“…2 More recent improvements in grafting and vector design have increased this to 30-40 days. 3,4 The levels of protein detected in plasma after transduced cells are transplanted to animals are much lower than predictions based upon the high levels of gene expression observed in the same cells in culture. 2 This might be due to cell death or might be caused by a problem of transport to the plasma, although transgenic studies have shown that when factor IX 5 and human growth hormone 6 are placed under the transcriptional control of keratinocyte-specific regulatory elements, protein is detected in the plasma.…”
Section: Introductionmentioning
confidence: 91%
“…This latter phenomenon of promoter down-regulation has also been proposed as the likely reason for short duration of Correspondence: GG Brownlee, Received 17 July 1997; accepted 27 October 1997 expression in keratinocytes in vivo. 3,8,9 However, owing to the technical difficulties in assaying for gene expression and cell survival in an intact graft over time in a quantitative manner, the theory of promoter downregulation remains controversial. Studies in other cells have shown that housekeeping or tissue-specific promoter/enhancers can increase the duration of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent loss of ␤-gal activity in SENCAR and CD-1 mice could be due to a decrease or loss of the viral promoter activity, [19][20][21][22] or a loss of transduced cells either by a failure to transduced stem cells or by immunological responses developed against the transduced cells. To examine the first possibility, LZRN-transduced skin was harvested 2 or 4 weeks after transduction.…”
Section: Loss Of Transgene Expression In Skin Of Sencar and Cd-1 Micementioning
confidence: 99%
“…32 Loss of RRV-mediated transgene expression in vivo has been reported in several systems including epidermal keratinocytes and attributed to inactivation of the viral promoter. [19][20][21][22] However, using an ex vivo approach, a recent study from this laboratory has demonstrated that the longevity of RRV-mediated expression in vivo is dependent upon transduction of stem cells in culture and no evidence of promoter inactivation could be obtained during a 20-week period in vivo. 27 In the present study we showed the feasibility of achieving long-term RRVmediated transgene expression in the absence of immunological responses to the transgene products.…”
Section: Figure 5 Persistent Expression Of Rrv-lzrn Transduced Keratimentioning
confidence: 99%